TikTok as an alternative assessment to enhance the oral production of storytelling in EFL chilean secondary classrooms - González Fuentes, Bárbara (Universidad de Santiago de Chile, 2022)
Integrantes: Bárbara González Fuentes, Alejandra Jiménez Roque, Tiare Reyes García, Milena Rivera Vásquez
Keywords: TikTok (Recurso electrónico); Inglés - Enseñanza - Hablantes extranjeros - Metodología; Redes sociales en Internet